Hypertrophic Cardiomyopathy in a Fetus: A Rare Presentation Case Report - Alireza Golbabaei; Elham sadat Alavi Moghaddam; Mahsa Naemi; Hooman Mohammad Talebi (Clinical Case Reports)
ABSTRACT A 34‐year‐old pregnant woman at 23 weeks of gestation was referred for fetal cardiomegaly, later diagnosed as fetal hypertrophic cardiomyopathy with left ventricular outflow tract obstruction. The neonate, delivered vaginally at 39 weeks, was treated with propranolol and has shown favorable progress under regular follow‐up.